Factors Affecting Mergers and Acquisitions in a Changing Environment - Andris DENINS (Communications of International Proceedings, 2020)
The purpose of this article is to set the main factors impecting the process of companies mergers and acquisitions. There are results of research explaned in this article. The research contents is arising from detailed wellknown scientists opinions review concerning companies mergers and acquisitions. On the bases of mathemacical statistics the author has set relationship between companies gained financial results and factors affecting process of mergers and acquisitions Statistical models have been elaborated by wich the efficiency of mergers and acquisitions is avaiilable assesed.
Keywords: Mergers; acquisitions; verticsl integration; horizontal integratin; mathematical statistics; regression analysis.